Pengembangan Sistem Pemantauan Pelayanan Kesehatan Bagi Penderita Hipertensi berbasis Web (Studi Kasus: Cafe DITA Puskesmas Karangan) - Azka Muhammad Hanisa; Komang Candra Brata; Mahardeka Tri Ananta (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
CafÃ© DITA (My Hypertension Diary; Information, Counseling, and Screening; Drug Inquiries and Consultations; Healthy Life Encouragement) is an innovation by Karangan Public Health Center to treat hypertension patients in the Karangan, Trenggalek. Cafe DITA monitors the patient's hypertension status using two documents, a register book, and a hypertension diary. CafÃ© DITA officers make monthly reports by manually determining the hypertension status and treatment status of each patient based on register books spread across 12 villages. The process of making this report takes time because it was only done by one person. Cafe DITA does not store the habits of each patient. It makes it difficult to analyze without the diary that each patient holds. Therefore this research was conducted to develop a system that can speed up the process of making reports and storing patient data at Cafe DITA. The development uses the waterfall SDLC. The system was implemented using PHP with Laravel framework. The result of unit testing and validation testing produces a 100% valid value. The efficiency test resulted in a 90,67% time decrease from testing report making of 50 patient data, so it can be concluded that making reports is faster using the system than making them manually.